Challenges Toward Practicing Lecturers’ Transformational Leadership at Public Universities in Afghanistan - Salarzai, Faridullah; Hasanzai, Masoud (Integrated Journal for Research in Arts and Humanities, 2023)
Transformational leadership has been widely investigated in business and educational sectors; however, little is known about its practices in a classroom setting. This study unveiled challenges toward practicing transformational leadership at public universities in Afghanistan by using a descriptive case study design of the qualitative method. The study used in-person interviews and classroom observations as research data collection instruments. The study also practiced the criterion technique of purposive sampling in order to select the right participants for the study. The interview data was saturated when the sample reached twelve participants, and used Nvivo12 for thematic analysis of the data. The result of the study showed that there are seventeen challenges when transformational lecturers practice transformational leadership in their working area.